Magnetic Field of a Ring-like Molecular Cloud - Dana Alina; Adel Umirbayeva; Yasuo Doi; Soichiro Jo; Yue Hu; Alex Lazarian; Janik Karoly; Tie Liu; Koji S. Kawabata; Alua Mukhash; Danial Zhumagayir; Tomori Hori; et al. (The Astronomical Journal)
We present a detailed study of the magnetic field structure in the G111 molecular cloud, a ring-like filamentary cloud within the NGC 7538 region. Our analysis combines multiwavelength polarization data and molecular-line observations to investigate the magnetic field’s role in the cloud’s formation and evolution. We utilized interstellar dust polarization from the Planck telescope to trace large-scale field orientations, starlight extinction polarization from the Kanata telescope to probe the cloud’s magnetic field after foreground subtraction, and velocity gradients derived from CO isotopologues observed with the IRAM 30 m telescope to examine dense regions. Our results reveal a coherent yet spatially varying magnetic field within G111. The alignment between Planck-derived orientations and starlight extinction polarization highlights significant foreground dust contamination, which we correct through careful subtraction. The global alignment of the magnetic field with density structures suggests that the field is dynamically important in shaping the cloud. Variations in CO-derived orientations further suggest that local dynamical effects, such as gravitational interactions and turbulence, influence the cloud’s structure. The curved magnetic field along the dense ridges, coinciding with mid-infrared emission in WISE data, indicates shock compression, likely driven by stellar feedback or supernova remnants. Our findings support a scenario where G111’s morphology results from turbulent shock-driven compression, rather than simple gravitational contraction. The interplay between magnetic fields and external forces is crucial in shaping molecular clouds and regulating star formation. Future high-resolution observations will be essential to further constrain the magnetic field’s role in cloud evolution.